Mapping the Healthcare Chaplaincy Literature: An Analytical Review of Publications Authored by Chaplains and Theologians Between 2000 and 2018. Issue 1 (2nd January 2020) - Poncin, Emmanuelle; Brandt, Pierre-Yves; Rouiller, François; Drouin, Mario; Dandarova Robert, Zhargalma
Abstract : The body of theoretical and empirical research led by chaplains and theologians between 2000 and 2018 is developing into a rich, diverse, and methodologically rigorous healthcare chaplaincy literature, which this review proposes to map. Online keyword and bibliographical searches and specialist recommendations yielded 199 relevant publications, which we analyzed in terms of methodology, topic, and results. On this basis, this article identifies and describes five key areas of the literature: chaplains' practices, spirituality, research, impact, and healthcare professionals' practices of spiritual care. The discussion further highlights that publications would benefit from greater conceptual clarity, common research standards, and more critical research designs.